Desenvolvimento de objetos simuladores para medicina nuclear - Ferreira, Fernanda Carla Lima (2011)
The phantoms used in Brazil are mostly imported and have relatively high financial cost. Although these phantoms can be considered as essentials for use in quality control, probably high quotas and import bureaucracy are obstacles to their acquisition by the nuclear medicine departments. The main objective of this work was the development of national phantoms for use in quality control of scintillation cameras used in nuclear medicine and for training professional personnel. Initially, we sought to know the interest of medical physicists and radiation protection supervisors in the acquisition of phantoms. After that, it was initiated the construction of three distinct types of physical phantoms, the SENCOR, to evaluate the sensitivity and the center of rotation; the SIMUFÍGADO, which is a liver phantom; and the ANTROFÍGADO, which is an anthropomorphic liver phantom in three versions. Besides these, we set up a computational phantom liver based on a physical phantom using Visual Monte Carlo. The conclusion obtained from inquiring professionals is that there is motivation for sharing and acquiring of national phantoms. The results obtained from characterization of materials used in the development of the phantoms should that such materials are suitable for the construction of such objects, observing only a change in color of acrylics irradiated with doses above 10 kGy. Through analysis of images of non anthropomorphic phantoms it is possible to study several parameters, such as sensitivity of the scintillation cameras, center of rotation, matrix size of pixels, the energy window, counting density and organs geometry. The images obtained from ANTROFÍGADO in SPECT and PET/CT systems can be useful to simulate the geometry of the healthy liver and cirrhotic liver, serving this object to the study of simulations of diagnostic analysis of location and evaluation of morphology and anomalies in the liver. Even though industrial processes for production of phantoms proposed here represent a significant increase in the final cost of these objects, it can be said that it is possible to reproduce many copies of these objects using the same methodology employed in the manufacture of the prototypes here studied.